The Power of Nostalgia in Creating Lovemarks for Brands - Philip, Sandy (AUC Knowledge Fountain, 2021)
Brand loyalty is a destination that most brands exert tedious attempts to achieve. Nostalgia, on another note, is encountered by most people worldwide in different contexts. Despite the vast research on nostalgia, little is known about the effect of nostalgia in creating authentic Lovemarks for historic places. Previous literature granted a clear and detailed understanding of the Lovemarks concept and the different forms and effects of nostalgia in various settings. To investigate the relationship between Lovemarks and Nostalgia, this study discerns the factors of Lovemarks in historical (Hotels, Restaurants, and Cafes) HORECA in Egypt to test their relation with Nostalgia Proneness (NP). Data were collected through interviewing HORECA managers, in addition to an online questionnaire with HORECA guests. Results illuminate the connection between nostalgia and Lovemarks through different aspects. Results also showed that Lovemarks factors slightly differ between hotels and cafes. The study concluded that nostalgia proneness is related to brand Lovemarks in many dimensions. This study is the impetus of a potential stream of research on the relation between nostalgia and Lovemarks. It contributes to future research by paving the way to the nostalgia effects on brand Lovemarks, which rose from some historical places in the land that started the pages of history: Egypt.